2018
DOI: 10.1186/s13014-018-0990-5
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment prognostic factors of survival and late toxicities for patients with nasopharyngeal carcinoma treated by simultaneous integrated boost intensity-modulated radiotherapy

Abstract: BackgroundTo scrutinize the pretreatment prognosticators on survival and late toxicities in a homogenous cohort of nasopharyngeal carcinoma (NPC) patients treated by simultaneous integrated boost intensity-modulated radiation therapy (SIB-IMRT).MethodsA total of 219 non-distant metastatic NPC patients consecutively treated by SIB-IMRT at a single institute were collected. The pretreatment factors including the socio-demographic variables, TNM stages, gross tumor volume (GTV), Epstein-Barr virus (EBV)-DNA, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…A possible reason for the impaired survival of patients with high viral-load is a missing or ineffective immune response due to immunosuppression or various cancer- and microenvironment-associated mechanisms, including alteration of regulatory T cell function and activation of the PD-1/PD-L1 axis (32, 33). Notably, similar findings have been reported for Epstein-Barr-Virus (EBV) associated nasopharyngeal cancer, where a high EBV-DNA load in the plasma correlated with an impaired outcome (34, 35).…”
Section: Discussionsupporting
confidence: 78%
“…A possible reason for the impaired survival of patients with high viral-load is a missing or ineffective immune response due to immunosuppression or various cancer- and microenvironment-associated mechanisms, including alteration of regulatory T cell function and activation of the PD-1/PD-L1 axis (32, 33). Notably, similar findings have been reported for Epstein-Barr-Virus (EBV) associated nasopharyngeal cancer, where a high EBV-DNA load in the plasma correlated with an impaired outcome (34, 35).…”
Section: Discussionsupporting
confidence: 78%
“…Similar findings have been reported by García‐Lorenzo et al and Burt et al Their conclusions are consistent with our findings. However, many studies have suggested that histological subtype does not influence the survival outcomes of patients with NPC . The reasons for the uncertain relationship between histological subtypes and the prognosis of NPC are presented below.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have suggested that histological subtype does not influence the survival outcomes of patients with NPC. [18][19][20] The reasons for the uncertain relationship between histological subtypes and the prognosis of NPC are presented below. 1) Because of the many classification schemes, it is difficult to compare studies, as the criteria for subclassifying a tumor vary from study to study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Guo et al (7) found that the maximal lymph nodal diameter measured in all the longitudinal, sagittal, and coronal planes was not a useful indicator in predicting the spread potential of NPC patients. It was suggested that the maximal lymph nodal diameter might not represent the tumor burden, which could be replaced by the tumor volume (15,16) and metabolic tumor volume (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%